Evaluation of the Implementation of Corporate Social Responsibility (CSR) Policies in Dumai City, Riau Province, Indonesia - Prihatin, Panca Setyo; Setiawan, Rizky; Wedayanti, Made Devi (SCAD Independent, 2024)
CSR as a form of corporate activity always demands social responsibility from companies. However, considering that the various types of CSR policies that currently exist have not been able to be implemented optimally by corporations, CSR policies need to be evaluated for systematic improvement. This research aims to determine the challenges companies face and how CSR policies can meet the policy evaluation criteria in Dumai City. This research uses qualitative research methods that explore challenges and evaluate CSR policies. Data analysis was conducted through the Nvivo 12 Plus application, sourced from interviews with each actor in Dumai City. This research found that the challenges companies face in CSR policies include the lack of a clear framework, lack of transparency and accountability, and difficulty balancing economic considerations with long-term needs. Then the evaluation of CSR policies in Dumai City is dominated by indicators of adequacy (21,62%) and equity (21,62%), followed by effectiveness (18,92%), responsiveness (16,22%), efficiency (13,51%), and accuracy (8.11%) which require optimal evaluation so that unclear rules regarding CSR policies can be improved systematically and able to achieve the important goals expected in the public sector.